4‐octyl Itaconate inhibits lipopolysaccharide (LPS)‐induced osteoarthritis via activating Nrf2 signalling pathway. Issue 5 (23rd January 2022) - Zhang, Qingchen; Bai, Xiaohui; Wang, Rongrong; Zhao, Hao; Wang, Lili; Liu, Jingwen; Li, Ming; Chen, Zheng; Wang, Zejun; Li, Lianxin; Wang, Dawei
Abstract: Small molecule drug intervention for chondrocytes is a valuable method for the treatment of osteoarthritis (OA). The 4‐octyl itaconate (OI) is a cellular derivative of itaconate with sound cell permeability and transformation rate. We attempted to confirm the protective role of OI in chondrocytes and its regulatory mechanism. We used lipopolysaccharide (LPS) to induce chondrocyte inflammation injury. After the OI treatment, the secretion and mRNA expression of Il ‐ 6, Il ‐ 10, Mcp ‐ 1 and Tnf ‐ α were detected by ELISA and qPCR. The protective effect of OI on articular cartilage was further verified in surgical destabilization of the medial meniscus model of OA. Cell death and apoptosis were evaluated based on CCK8, LDH, Typan blue staining, Annexin V and TUNEL analyses. The small interfering RNAs were used to knockout the Nrf2  gene of chondrocytes to verify the OI‐mediated Nrf2 signalling pathway. The results revealed that OI protects cells from LPS‐induced inflammatory injury and attenuates cell death and apoptosis induced by LPS. Similar protective effects were also observed on articular cartilage in mice. The OI activated Nrf2 signalling pathway and promoted the stable expression and translocation of Nrf2 into the nucleus. When the Nrf2 signalling pathway was blocked, the protective effect of OI was significantly counteracted in chondrocytes and a mouse arthritis model. Both itaconate and its derivative (i.e., OI) showed important medical effects in the treatment of OA.